Pelatihan Kepemimpinan Karang Taruna Menuju Generasi Muda Mandiri Desa Genting Kabupaten Semarang (Lembaga Pengembangan Kinerja Dosen, 2026)
The objectives of this community service activity are: First, to increase members' understanding of the concepts of leadership and effective organizational governance. Second, to strengthen the capacity of youth in entrepreneurship. Third, to equip them with the skills to develop innovative and adaptive work programs tailored to local needs. The methods used in this activity include workshops focused on delivering theoretical material, practical technical guidance or training applied to train participants in effective leadership and good organizational management, and mentoring methods implemented using a participatory approach. The evaluation of the activity showed significant improvements in knowledge, skills, and attitudes across three aspects that have historically hindered partners: education, social issues, and economics. In conclusion, there was a significant improvement overall after the community service activity, at 56%. The highest level of understanding among participants is the importance of leadership as a driving force for the organization, but to develop an entrepreneurial attitude as a foundation for independence and competitiveness, continuous reinforcement is needed so that Karang members can be prepared as an independent generation.